Motoricko ucenje u sportu - Coh, M.; Jovanovic-Golubovic, D.; Bratic, M. (Facta Universitatis: Series Physical Education and Sport, 2004)
Motor learning is characterised by specific features and it incorporates laws that have to be observed throughout the various manifestations of an athlete?s motor activity. It is the process of acquiring, completing and using motor information, knowledge, experience and motor programs. Performing a certain movement is only possible if a suitable motor programme for it exists. The motor process starts with a definition of the desired result and consists of three interconnected phases: the phase of basic movement coordination, the phase of accurate movement coordination and the phase of movement coordination stabilisation under changeable and difficult circumstances. A precondition for efficient motor learning is an optimally accurate notion of movement which is based on the visual followed by the kinesthetic processing of information.